Environmental, Social, and Governance Performance and Value Creation in Product Market: Evidence from Emerging Economies - Yasmeen, Bashir; Yiwei, Zhao; Huan, Qiu; Zeeshan, Ahmed; Josephine Yau, Tan Hwang (MDPI, 2023)
Using a unique sample of 13,412 firm-year observations from 19 countries of the emerging economies for the period of 2011 to 2019, we investigate the association between the firms’ environmental, social, and governance (ESG) performance and their value creation in the product market. Specifically, we first used the pooled OLS regression model for panel data as our baseline model and found that ESG performance (as well as its pillars) has a strong positive effect on the future value creation of the firms in the product market. We also conducted some additional analyses using various regression models, as well as adopting multiple tests for endogeneity, and the additional analyses revealed that the results are robust under different scenarios. Overall, the findings of this study highlight the importance of firm-level ESG performance for the value creation of firms in the product market in emerging economies and have theoretical and practical implications for academic researchers, market participants, and government entities in studying, evaluating, and governing firms’ ESG performance and reporting.